1997
DOI: 10.1038/nm1197-1250
|View full text |Cite
|
Sign up to set email alerts
|

HIV-specific mucosal and cellular immunity in HIV-seronegative partners of HIV-seropositive individuals

Abstract: HIV-specific mucosal and cellular immunity was analyzed in heterosexual couples discordant for HIV status in serum and in HIV-unexposed controls. HIV-specific IgA but not IgG was present in urine and vaginal wash samples from HIV-exposed seronegative individuals (ESN), whereas both IgA and IgG were observed in their HIV-seropositive partners; antibodies were not detected in low-risk controls. Envelope protein (Env) peptide-stimulated interleukin-2 (IL-2) production by peripheral blood mononuclear cells (PBMCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
216
4
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 374 publications
(228 citation statements)
references
References 51 publications
5
216
4
3
Order By: Relevance
“…This observation deserves several considerations. First of all, as previously demonstrated in adults exposed to HCV and to other viral infections [6,11], it seems to confirm that the evaluation of T-cell reactivity may represent a useful tool in revealing previous exposures of the host to a viral agent. Hence, T-cell reactivity is able to detect a component of the immune response that is not revealed when considering antibody seroconversion solely.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This observation deserves several considerations. First of all, as previously demonstrated in adults exposed to HCV and to other viral infections [6,11], it seems to confirm that the evaluation of T-cell reactivity may represent a useful tool in revealing previous exposures of the host to a viral agent. Hence, T-cell reactivity is able to detect a component of the immune response that is not revealed when considering antibody seroconversion solely.…”
Section: Discussionsupporting
confidence: 72%
“…One peptide from the core (C39-63), one from the envelope (E 1 238-262), and two from the non-structural region (NS 3 1384-1401, and NS 3 1406-1415) resulted to be the most immunogenic in preliminary experiments, and were therefore used along this study to analyze HCV-specific T-cell reactivity. A nonantigenic HIV peptide (p23) was used as negative control [8].…”
Section: Hcv-peptidesmentioning
confidence: 99%
“…Although persistence of HIV-specific IgA and IgM in breast milk was associated with reduced transmission in one study in Rwanda, 10 no protective association was observed in two other studies. 8,11 HIV-specific sIgA has been detected frequently in cervicovaginal samples from exposed but persistently uninfected cohorts of high-risk women, [12][13][14] suggesting a role for these mucosal responses in resistance to HIV. Purified sIgA from exposed-uninfected women has been shown to neutralize a variety of HIV subtypes and phenotypes 15,16 and to block transcytosis.…”
mentioning
confidence: 99%
“…There are also some individuals who remain seronegative despite high risk and/or multiple exposures to HIV-1. These exposed seronegatives (ES) include infants born to HIV-1 infected mothers [5][6][7], commercial sex workers in epidemic areas [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], hemophiliacs who received HIV contaminated factor VIII preparations [26,27], and sexual partners of known HIV-1 infected persons [28][29][30][31][32][33]. Understanding the mechanisms that account for slower disease progression in LTNP and the protection against HIV-1 infection observed with ES is important for the development of more potent therapeutic regimens and a vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that both viral and host factors may contribute to these outcomes. Acquired immune responses, including cellular [5, 8-11, 14, 15, 17, 26, 28, 34-37] and humoral [10,16,20,[38][39][40][41][42][43][44] responses to HIV-1, may play an important role in protecting against and controlling HIV-1 infection. Significant studies in the past few years have also demonstrated that innate immunity including genetic polymorphisms in host genes can affect the risk for HIV-1 infection and disease progression (Tab.…”
Section: Introductionmentioning
confidence: 99%